Plasma Circulating Tumor Epstein–Barr Virus for the Surveillance of Cancer Progression in Bone-Only Metastatic Nasopharyngeal Carcinoma - Liu, Guo-Ying; Xia, Wei-Xiong; Bi, Zhuo-Fei; Lu, Nian; Li, Wang-Zhong; Bei, Wei-Xin; Liang, Hu; Xie, Jun-Zhi; Liu, Yi-Min; Yao, He-Rui; Xiang, Yan-Qun (Frontiers in Oncology, 2022)
Abstract: Background: Plasma Epstein-Barr virus DNA (EBV-DNA) is a sensitive and specific biomarker for nasopharyngeal carcinoma (NPC). We investigated whether longitudinal monitoring of EBV-DNA could accurately detect clinical disease progression in NPC patients with bone-only metastases. Methods: In this retrospective study, a total of 105 patients with bone-only metastatic NPC who were treated with platinum-based first-line chemotherapy were enrolled. Undetectable EBV-DNA after first-line chemotherapy was defined as biochemical complete response (BCR). The correlation of the EBV-DNA dynamic status with overall survival (OS) and progression-free survival (PFS) were determined by Cox regression. The correlation between non-normalized EBV-DNA period and PFS period were determined. Results: After a median follow-up time of 53.4 months (IQR: 42.8-80.6), 64 patients had disease progression. Thirty-nine of 105 patients (37.1%) had BCR at all follow-up time points and none of these 39 patients had disease progression, corresponding to a negative predictive value (NPV) of 100%. Sixty-six patients had a detectable EBV-DNA during surveillance, with 64 diagnosed as disease progression at last follow-up, for a positive predictive value (PPV) of 97.0%. Actuarial 3-year OS rates were 45.0% for patients with detectable EBV-DNA during posttreatment surveillance and 100% for patients with undetectable EBV-DNA. Lastly, median lead time between non-normalized EBV-DNA and clinical-proven progression was 5.87± 0.67 months. Conclusions: Taken together, EBV-DNA provided predictive value regarding progression of bone-only metastatic NPC patients. The clinical impact should be confirmed in prospective randomized studies.